2018
DOI: 10.1074/jbc.ra118.004652
|View full text |Cite
|
Sign up to set email alerts
|

Ligand binding and heterodimerization with retinoid X receptor α (RXRα) induce farnesoid X receptor (FXR) conformational changes affecting coactivator binding

Abstract: Edited by Dennis R. VoelkerNuclear receptor farnesoid X receptor (FXR) functions as the major bile acid sensor coordinating cholesterol metabolism, lipid homeostasis, and absorption of dietary fats and vitamins. Because of its central role in metabolism, FXR represents an important drug target to manage metabolic and other diseases, such as primary biliary cirrhosis and nonalcoholic steatohepatitis. FXR and nuclear receptor retinoid X receptor ␣ (RXR␣) form a heterodimer that controls the expression of numerou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 38 publications
2
46
0
Order By: Relevance
“…Like most NRs, FXR has a N terminal ligandindependent activation function (AF1), a highly conserved DNA-binding domain (DBD), a ligand binding domain (LBD), and finally a C-terminal ligand-dependent activation function (AF2) (51). FXR forms a heterodimer with retinoid X-receptor (RXR), and when there is no ligand binding, the FXR-RXR heterodimer remains bound to FXR responsive elements (FXREs) within the promoters of FXR target genes, bound to co-repressors (52). Upon ligand-induced activation, corepressors leave the FXR-RXR heterodimer to make way for co-activators, thus upregulating target gene transcription (52).…”
Section: Microbiota As a Modulator Of Hepatic Lipid Homeostasis Via Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Like most NRs, FXR has a N terminal ligandindependent activation function (AF1), a highly conserved DNA-binding domain (DBD), a ligand binding domain (LBD), and finally a C-terminal ligand-dependent activation function (AF2) (51). FXR forms a heterodimer with retinoid X-receptor (RXR), and when there is no ligand binding, the FXR-RXR heterodimer remains bound to FXR responsive elements (FXREs) within the promoters of FXR target genes, bound to co-repressors (52). Upon ligand-induced activation, corepressors leave the FXR-RXR heterodimer to make way for co-activators, thus upregulating target gene transcription (52).…”
Section: Microbiota As a Modulator Of Hepatic Lipid Homeostasis Via Fmentioning
confidence: 99%
“…FXR forms a heterodimer with retinoid X-receptor (RXR), and when there is no ligand binding, the FXR-RXR heterodimer remains bound to FXR responsive elements (FXREs) within the promoters of FXR target genes, bound to co-repressors (52). Upon ligand-induced activation, corepressors leave the FXR-RXR heterodimer to make way for co-activators, thus upregulating target gene transcription (52). While FXR was initially found to be weakly activated by farnesoid, an intermediate of mevalonate metabolism, it was later found that despite low affinity, BAs potently activate FXR in the order of CDCA > LCA = DCA > CA (53).…”
Section: Microbiota As a Modulator Of Hepatic Lipid Homeostasis Via Fmentioning
confidence: 99%
“…An emerging therapeutic target for NAFLD is the farnesoid X receptor (FXR, encoded by NR1H4 ), a transcription factor that regulates lipid and glucose metabolism and hepatic inflammation. FXR activation induces the expression of genes involved in lipoprotein metabolism/clearance and represses the activity of genes involved in triglyceride synthesis . The main mechanism mediating these effects is inhibition of lipogenesis and induction of beta‐oxidation .…”
Section: Introductionmentioning
confidence: 99%
“…FXR activation induces the expression of genes involved in lipoprotein metabolism/clearance and represses the activity of genes involved in triglyceride synthesis. 8,9 The main mechanism mediating these effects is inhibition of lipogenesis 10,11 and induction of beta-oxidation. 12 However, the regulatory effects of FXR on 1-deoxysphingolipid metabolism have never been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Farnesyl X receptor (FXR) is related with bile acid metabolism, which is important in bile acid secretion. In former experiment we have detected that bile salt export pump (Bsep), a target gene of FXR,expression decreased in hilar cholangiocarcinoma tissues of rats, which led us to investigate the role of FXR, whether the role of FXR is enhanced or diminished in hilar cholangiocarcinoma [1][2][3].…”
Section: Introductionmentioning
confidence: 99%